In the Heart of CLIL: Materials and Methods. A Manual for Secondary School Teachers - Mortimore, Louisa (Pulso. Revista de educación, 2019)
Review of the book:  Ting, & Martínez Serrano, L. M. (2018). En el corazón de AICLE : materiales y métodos : manual para profesorado de Educación Secundaria. UCOPress.